Hakkâri’de Yapılandırmacı Sosyal Bilgiler Dersi Öğrenme Ortamlarına İlişkin Bir Değerlendirme: Değişim Kolay Mı? - (:unkn) unknown (My University, 2016)
Bu araştırmada, Hakkâri'de sosyal bilgiler dersi öğretme-öğrenme süreçlerinin yapılandırmacı öğrenme yaklaşımına uygun olup olmadığı öğretmen görüşleri ve sınıf içi uygulamaları çerçevesinde incelenmiştir. Nitel araştırma tasarımı kullanılan çalışmada, katılımcıların seçiminde amaçlı örneklem seçiminden yararlanılmıştır. Verilerin toplanmasında yarı yapılandırılmış görüşme formu ve gözlem formu kullanılmıştır. Hakkâri il merkezinde görev yapan 25 sosyal bilgiler öğretmeni ile görüşme gerçekleştirilmiştir. Görüşme yapılan öğretmenlerden 6 öğretmenin altışar saatten toplam 36 saat dersleri gözlemlenmiştir. Elde edilen verilerin çözümlenmesinde içerik analizi yöntemi kullanılmıştır. Araştırma sonuçları, politik, sosyo-kültürel, ekonomik ve coğrafi etkenlerden dolayı Hakkâri'de sosyal bilgiler öğrenme-öğretme süreçlerinde yapılandırmacı öğrenme anlayışının oluşturulamadığını ortaya koymuştur

The present study aims to examine the way in which social studies learning environments based on the constructivist view implemented in schools in Hakkari. The qualitative research designs were adopted in the study where participants were selected via purposive sampling. Data were collected via semi-structured interviews with social studies teachers and classroom observations. A group of (n=25) the social studies teachers who work in schools located in the province of Hakkari were interviewed face-to-face regarding how they implement social studies curriculum in their classes. Six of these teachers were also selected for classroom observations. Each teacher was observed for 6 teaching hour. Thereby, a total of 36 social studies teaching hour was observed. Content analysis method was used in analyzing the qualitative data obtained via interviews and observations. Findings of the study indicated that the constructivist teaching environments could not be created in the social studies courses in schools in Hakkari due to political, socio-cultural, geographical, economical factors
An Evaluation of Constructivist Learning Environments In Social Studies Courses in Hakkari: Is The Transition Easy?
Keywords: Matematik; Eğitim, Eğitim Araştırmaları